Presence of steroid hormones in Lake Titicaca and drinking water, Puno (Peru) - Zamalloa-Cuba, Walter (2021)
The presence of steroid hormones in lake waters causes contamination of aquatic ecosystems, which may cause endocrine alterations in the organisms that inhabit them. Moreover, many of these waters are purified and distributed to populations located around the lake; therefore, these effects could be repeated in humans who consume these waters. This study reports the presence of steroid hormone residues in the waters of the inner bay of Lake Titicaca and drinking water in the city of Puno-Perú. The Solid phase extraction method was used for sample preparation, and the analyses were developed in an HPLC-DAD system. Results show maximum concentrations of steroid hormones estrone (E1) 1.56, 17 β- estradiol (E2) 2.27, 17 α- ethinylestradiol (EE2) 13. 88 ng L-1 respectively. These concentrations vary at the different monitoring points, and their presence could cause ecotoxicological effects to the endemic aquatic biota that inhabit this part of this lake; at the same time they also could affect the health of the human population that consumes this water